Auricular Electrical Stimulation Alleviates Headache through CGRP/COX-2/TRPV1/TRPA1 Signaling Pathways in a Nitroglycerin-Induced Migraine Rat Model - Liao, Chung-Chih (Evid Based Complement Alternat Med, 2019)
The study aimed to investigate effect of auricular electrical stimulation (ES) on migraine. Migraine was induced in rats by intraperitoneal administration of nitroglycerin (NTG, 10 mg/kg) three times. Auricular ES pretreatment was performed for five consecutive days. Migraine behaviors were observed by a video recording. Auricular ES pretreatment could reverse the decrease of the total time spent on exploratory (2619.0 ± 113.0 s vs 1581.7 ± 217.6 s, p=0.0029) and locomotor behaviors (271.3 ± 21.4 s vs 114.3 ± 19.7 s, p=0.0135) and also could reverse the increase of the total time spent on resting (19.0 ± 10.6 s vs 154.3 ± 46.5 s, p=0.0398) and grooming (369.9 ± 66.8 s vs 1302.0 ± 244.5 s, p=0.0324) behaviors. Auricular ES pretreatment could increase the frequency of rearing behaviors (38.0 ± 1.8 vs 7.7 ± 3.5, p < 0.0001) and total distance traveled (1372.0 ± 157.9 cm vs 285.3 ± 85.6 cm, p < 0.0001) and also could increase the percentage of inner zone time (6.0 ± 1.6% vs 0.4 ± 0.2%, p=0.0472). The CGRP, COX-2, TRPV1, and TRPA1 immunoreactive cells in the trigeminal ganglion increased in the NTG group compared with the control group (all p < 0.0001); this increase could, however, be reduced by auricular ES pretreatment (27.8 ± 2.6 vs 63.0 ± 4.2, p < 0.0001; 21.7 ± 1.2 vs 61.8 ± 4.0, p < 0.0001; 24.3 ± 1.0 vs 36.5 ± 1.7, p=0.0003; and 20.7 ± 1.9 vs 90.8 ± 6.5, p < 0.0001, respectively). Therefore, we suggest that auricular ES pretreatment is beneficial for the treatment of migraine and this effect is partly related to CGRP/COX-2/TRPV1/TRPA1 signaling pathways.